Paperboard mill wastewater treatment via combined dark and LED-mediated fermentation in the absence of external chemical addition. (January 2020) - Elsharkawy, Khaled; Gar Alalm, Mohamed; Fujii, Manabu; Afify, Hafez; Tawfik, Ahmed; Elsamadony, Mohamed
Graphical abstract: Highlights: Long HRT for dark fermentation process accounted for higher CO2 production. Proposed light configuration led to light conversion efficiency augmentation to 5.9%. Optimum overall performance was acquired at HRT of 12 h with HP of 1394.1 mL/L/d. Growth rate of photosynthetic bacteria was higher than dark fermentative bacteria. Abstract: Paperboard mill wastewater (PMWW) was treated using two subsequent dark and photo up-flow intermitted stirring tank reactors (UISTRs) under different hydraulic retention times (HRTs) without external chemical use. HRT of 12 h revealed the maximum overall H2 productivity of 1394.1(±70.6) mL/L/d with contents of 48.9(±2.5) and 47.4(±1.4)% for dark- and photo-processes, respectively. Overall substrate removal efficiency (SDE) of 58.9(±4.5)% was registered at HRT o 12 h. High H2 productivity was ascribed to fermentation type occurred at dark reactor, since acetate and butyrate accounted for 70.9% of volatile fatty acids. Besides, pH and carbon to nitrogen ratio of dark reactor's effluent at HRT = 12 h were 5.5(±0.1) and 30.0(±2.5), respectively which are the optimum levels for photo fermentation process. Moreover, energetic and economic analyses emphasized on the superiority of 12 h-HRT, where net gain energy, daily saving and payback period accounted for 1319.5 kWh/d, 148.7 $/d and 9.8 years, respectively.